Generational Preferences and Willingness to Pay for Antioxidant-Rich Pomegranates: Insights into Consumer Behavior and Market Potential - Anna Uliano; Marco Lerro (Agriculture)
This study investigates consumer preferences and willingness to pay (WTP) for antioxidant-rich pomegranates, focusing on the roles of product attributes and generational differences. A survey of 3019 Italian consumers assessed consumption habits, perceived barriers, and WTP for antioxidant-enriched pomegranates. A Best–Worst Scaling (BWS) analysis was used to identify key product attributes, and generational segmentation highlighted differences in consumer behavior. The results reveal a strong preference for locally sourced pomegranates and a high valuation of health-related attributes, particularly antioxidant content. However, several consumption barriers emerged, including taste preferences, peeling difficulty, and limited product availability. While older generations, especially Baby Boomers, prioritize antioxidants for their health benefits, younger generations (Gen Z and Millennials) showed the highest WTP for antioxidant-enriched pomegranates, likely influenced by novelty seeking and engagement with food trends. These findings suggest that marketing strategies should emphasize both local origins and health benefits. From a policy perspective, supporting local agriculture and promoting the nutritional value of enriched foods could enhance consumer acceptance and expand the market potential.